Redo axillary artery cannulation in aortic reoperations: Technical variations and implications for optimal outcomesCentral MessagePerspective - Suguru Ohira, MD, PhD; Gabrielle Amar, BA; Sooyun Caroline Tavolacci, MD, MSCR; Masashi Kai, MD; Ramin Malekan, MD; Junichi Shimamura, MD, PhD; Steven L. Lansman, MD, PhD; David Spielvogel, MD (JTCVS Techniques)
Objectives: Recannulation of the right axillary artery (Redo-AX) is a valuable yet underutilized technique in aortic reoperations. The present study sought to analyze the outcomes of 1 of the largest redo AX cannulations experiences. Methods: From February 2005 to December 2024, AX cannulation was planned for 804 aortic repairs and analyzed according to the intention-to-treat principle. Fifty patients had Redo-AX, whereas 754 patients had primary AX cannulation. Cannulation-related events included technical failure, vascular injury, additional vascular rep, and iatrogenic retrograde dissection. Results: This cohort included 196 redo sternotomies (24.4%) and 381 type A aortic dissections (47.4%). Among the 50 Redo-AX procedures, 46 patients had direct AX cannulation, and 4 patients had the side-graft technique in their initial surgery. Forty-five patients were successfully cannulated for cardiopulmonary bypass. Two patients underwent the side-graft technique with a graft extension, and direct AX cannulation was performed in 43 patients via arteriotomy (n = 40), the Seldinger technique (n = 2), and direct cannulation through an old polyethylene terephthalate graft (n = 1). The overall rate of cannulation-related events was 2.1% (17 out of 804), and the rate of cannulation site shift was 2.7% (22 out of 804). Cannulation-related events (10% vs 1.6%; P < .001) were significantly more common in the Redo-AX group. Operative mortality was comparable between groups (Redo-AX, 0% vs Primary-AX, 4.8%; P = .220), as was the incidence of stroke (0% vs 4.9%, P = .209). Conclusions: Redo-AX is a durable approach for complex redo aortic cases. Careful preoperative evaluation and certain surgical expertise are paramount to achieving optimal outcomes.